Assessing the level and sources of Polycyclic Aromatic Hydrocarbons (PAHs) in soil and sediments along Jhelum riverine system of lesser Himalayan region of Pakistan. (February 2019) - Riaz, Rahat; Ali, Usman; Li, Jun; Zhang, Gan; Alam, Khan; Sweetman, Andrew James; Jones, Kevin C.; Malik, Riffat Naseem
Abstract: Lesser Himalayan Region (LHR) is an important mountain ecosystem which supports a wide range of biodiversity for native flora and fauna. Human population in this region is largely dependent upon local sources for their livelihood. Surface soil (n = 32) and sediment (n = 32) were collected from four different altitudinal ranges of LHR and analyzed for priority Polycyclic Aromatic Hydrocarbons (PAHs) recommended by USEPA. Level, sources and distribution pattern of PAHs were assessed in soil and sediments samples collected from four altitudinal zones in LHR. Total PAHs concentration level of PAHs in soil and sediments ranged from 62.79 to 1080 ng g −1 and 14.54–437.43 ng g −1, respectively. Compositional profile of PAHs in both soil and sediment were dominated by low and medium molecular weight PAHs, ranged from 18.02 to 402.18 ng g −1 in soil and 0.32–96.34 ng g −1 in sediments. In the context of spatial distribution trend, highest mean concentrations of PAHs in soil were recorded in zone D (sites from the rural region) and for sediments highest concentrations were detected at zone A, which includes dam sites. In all four zones, no altitudinal trend of PAHs in soil and sediments was observed. Source apportionment through receptor modelling by positive matrix factorization (PMF) revealed that local sources such as biomass combustion and vehicular emissions are important sources of PAHs in this region. The prevalence of monsoon atmospheric circulation system in LHR implicated that this region is also influenced by medium and long range atmospheric transportation of PAHs from neighboring countries where potential sources and high level of PAHs has been reported. Graphical abstract: Highlights: Polycyclic Aromatic Hydrocarbons (PAHs) were assessed in soil and sediments of the Lesser Himalayan Region (LHR). High concentration of PAHs were observed in urban and sub-urban regions. Biomass combustion and vehicular emissions are important sources of PAHs in LHR.